The Effects of Interval Training on The V02max on The Basket Ball Players - Fekie Adila; Ittaqwa Ittaqwa; Muhammad Khozin; Khoirul Fatihin; Triatmo Joko Purnomo (Journal of Coaching and Sports Science, 2023)
Endurance plays an active role in basketball games as a support for implementing strategy and tactics, so players must have excellent endurance. The study aims to determine the impact of interval training on high school basketball players' endurance. The research applied the experimental method. The samples are ten participants of the As-Shofa basketball team determined through a total sampling technique. The research uses the one-group pretest-posttest design. The instrument in this study is a bleep test. Based on the test analysis, the tcount value obtained was 2,371, and the ttable value obtained was 1,833. These values indicate that the tcount value is greater than the ttable at a 0,05 sig. value. The results of this study can conclude a significant influence of interval training exercises on high school basketball players' endurance. The determinant value of endurance is 67 percent contribution. Thus, high-intensity interval training significantly increases the Vo2max endurance capacity.